Effect of Types and Doses of Compost Fertilizer on Growth and Yield of Sawi Plants (Brassica juncea L.). - Sudirman Almi; Noor Jannah (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
This study aims to determine the effect of compost types and doses of compost fertilizer and their interactions on the growth and yield of mustard greens. To find out the dosage of compost suitable for mustard plants.The study was conducted in Bukit Makmur Village, Kaliorang District, East Kutai Regency. The research was conducted from May to June 2015. Starting from May 1, 2015 to June 15, 2015.The study used a Factorial 3x4 Complete Randomized Design (RAL) pattern which was repeated 4 (four) times. The first factor is the type of compost fertilizer (K) which consists of 3 (three) levels, namely: cow manure compost (k1), chicken manure compost (k2), and goat manure compost (k3). The second factor was the dose of compost (D) which consisted of 4 (four) levels, namely: without giving doses of compost fertilizer (d0), 35 g / polybag compost (d1), 52.5 g / polybag compost (d2) and 70 g / compost poly bag (d3).The treatment of compost types was significantly different from the wet weight of mustard plants, but it was not significantly different from plant height, number of leaves aged 2, 4 and 6 weeks after planting, and dry weight of mustard plants.The treatment of compost dosage was significantly different for plant height, but it was not significantly different from the number of leaves aged 2, 4 and 6 weeks after planting, wet weight and dry weight of mustard plants.The interaction between types of compost and the dosage of compost differed significantly from plant height, number of leaves aged 2, 4 and 6 weeks after planting, wet weight and dry weight of mustard plants